2004
DOI: 10.1097/01.ede.0000121380.02594.fc
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection Byproducts and Bladder Cancer

Abstract: These findings strengthen the hypothesis that the risk of bladder cancer is increased with long-term exposure to disinfection byproducts at levels currently observed in many industrialized countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
273
0
10

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 484 publications
(284 citation statements)
references
References 36 publications
1
273
0
10
Order By: Relevance
“…2,3 Experimental evidence has suggested that the mechanisms behind DBP carcinogenicity may partially be explained by epigenetic alterations that result from chronic cytotoxicity mediated by a mixture of oxidative metabolites release, reductive free radicals, and cell integrity disruption. 5,32 For non-genotoxic compounds, cycles of mitotic regeneration in response to cytotoxicity may produce cumulative epigenetic changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Experimental evidence has suggested that the mechanisms behind DBP carcinogenicity may partially be explained by epigenetic alterations that result from chronic cytotoxicity mediated by a mixture of oxidative metabolites release, reductive free radicals, and cell integrity disruption. 5,32 For non-genotoxic compounds, cycles of mitotic regeneration in response to cytotoxicity may produce cumulative epigenetic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Trihalometanes (THMs) are one of the most abundant classes in chlorinated waters; in the past, Spain has shown high levels of THMs compared to Northern Europe. 1 Lifetime exposure to DBPs has been related to bladder cancer 2,3 and, possibly, colorectal cancer 4 in epidemiological studies. However, the mechanisms involved in these deleterious effects are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiological studies suggest a link between consumption of chlorinated drinking water and reproductive and developmental outcomes, such as increased spontaneous abortions and intrauterine growth retardation [10][11][12][13][14], and bladder and gastrointestinal tract cancers [15][16][17][18][19][20][21]. At present, which by-products in chlorinated drinking water could be responsible for increasing cancer risk in human beings is not well established, because the potential synergistic interactions of chlorinated by-products and their role in the molecular mechanisms of carcinogenesis are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to disinfection by-products (DBPs) has been associated with an increased risk of bladder cancer (Villanueva et al, 2004), and, while there might also be an association with adverse reproductive outcomes, the nature of this potential effect remains unclear (Nieuwenhuijsen et al, 2000a;Graves et al, 2001;Bove et al, 2002). Many of the epidemiological studies have relied on approximate measures of DBP exposure, such as concentration in the study subject's municipal water source, potentially resulting in substantial exposure misclassification.…”
Section: Introductionmentioning
confidence: 99%